The Governance of Sport. Issue 1 (2nd January 2017) - Kreft, Lev
Abstract: Political philosophy is an examination of distribution of power in human communities and institutions. In previous period when identity issues were the most important political approach philosophy of sport had to deal mostly with discrimination and much less with the distribution of power in sport governance. Recent scandals revealed that at the top of sport governing bodies. Even more: it exposed the political character of the distribution of unleashed power in sport. That is why it is not enough to punish ad to prevent. It is necessary to change the distribution of power, reform the models of control over political power in sport and to rethink the whole system of governance in sport. The proposal of this paper is just one short step in this direction with two points of departure: a change in initial sport's associational character of aristocratic distribution of power into contemporary state of corporation with managerial distribution of power; and political philosophy's proposals for models of democratic control at the global level.